Perinatal complications and schizophrenia: involvement of the immune system - Jenkins, Trisha A. (Frontiers in Neuroscience, 2013)
The neurodevelopmental hypothesis of schizophrenia suggests that, at least in part, events occurring within the intrauterine or perinatal environment at critical times of brain development underlies emergence of the psychosis observed during adulthood, and brain pathologies that are hypothesised to be from birth. All potential risks stimulate activation of the immune system, and are suggested to act in parallel with an underlying genetic liability, such that an imperfect regulation of the genome mediates these prenatal or early postnatal environmental effects. Epidemiologically based animal models looking at environment and with genes have provided us with a wealth of knowledge in the understanding of the pathophysiology of schizophrenia, and give us the best possibility for interventions and treatments for schizophrenia.